Estimating the Costs and Benefits of a Common Currency for the Second West African Monetary Zone (WAMZ) - Okafor, Harrison Oluchukwu (Journal of Economics and Behavioral Studies, 2013)
This paper, estimates the costs and benefits of a common currency in WAMZ. Behavioral models capturing the elements of costs (asymmetric shocks, loss of monetary policy autonomy, and fiscal policy distortion), and benefits (trade creation, financial integration effects and policy coordination gains) were estimated using the Vector Auto-regression (VAR) procedure and panel estimation technique.VAR impulse response and forecast error method was used to determine the countries’ response to shocks while panel regression technique was used to estimate other behavioral equations. Fiscal policy distortion and loss of monetary policy autonomy are the main cost of monetary union in the zone while the potential trade creation gain is marginal. High disposition to money reserve and weak revenue base are the core determinants of fiscal policy distortion in the zone. Overall, the paper concludes that fiscal policy distortion constitutes serious policy challenge to monetary union in the zone. Dealing with this challenge may require short-run systematic macroeconomic adjustments to enhance the convergence of macroeconomic policy indicators in the zone.